The effect of omentectomy on the blood levels of adipokines in obese patients with endometrial cancer. Issue 3 (May 2022) - Comba, Cihan; Ozdemir, Isa Aykut; Demirayak, Gokhan; Erdogan, Sakir Volkan; Demir, Omer; Özlem Yıldız, Güneş; Bulut, Huri; Karakas, Sema; Gulseren, Varol; Afsar, Selim; Gungorduk, Kemal
Abstract: Objective: To investigate the blood levels of adipokines in obese patients with endometrial cancer who have and have not undergone omentectomy. Methods: Between September 2017 and September 2019, the study recruited 54 patients with endometrial cancer. Measurements were taken of blood levels of human leptin, perilipin-1, adiponectin, adipolin, resistin, visfatin, and estrone preoperatively and postoperatively before adjuvant therapy or at the end of one month. The serum samples were separated by centrifugation for 10 mins at 3, 000 revolutions/min, then stored at −80 °C until assay. Results: In this prospective study, a total of 54 endometrial cancer patients were analyzed in two separate groups according to the omentectomy status. Comprehensive staging surgery with omentectomy and without omentectomy was performed in 26 patients and 28 patients, respectively. The age, body mass index, body fat index, waist circumference, and skin thickness values of the patients with and without omentectomy were found to be similar. No statistically significant difference was determined between the patients with and without omentectomy in respect of the blood level of the adipokines measured preoperatively. A strong statistically significant correlation was determined between the pre and postoperative levels of Human Leptin (p = 0.002), perilipin-1(p = 0.001), adipolin (p < 0.001), adiponectin (p < 0.001), resistin (p = 0.001), visfatin (p < 0.001), and estrone (p = 0.004) (r = −0.43, −0.47, 0.75, 0.84, −0.47, - 0.58, −0.41, respectively) Conclusions: Omentectomy affected the postoperative blood levels of adipokines in obese patients with endometrial cancer. As omentectomy may have some positive effects on metabolism in these patients, it may be considered during endometrial cancer surgery due to the possible positive metabolic effects. Highlights: The coexistence of endometrial cancer with obesity is common. Omentectomy changed blood levels of adipokines. Adipokines have a critical role on the metabolism of glucose or lipid